Production and characterization of biodiesel from Argemone mexicana seed oil - Melese Damtew Asfaw; Adamu Tizazu Yadeta; Betelihem Gessese Yewalie; Yosef Wondossen Negash (Results in Chemistry)
This study investigates the potential of A. mexicana seeds as a feedstock for biodiesel production. The oil was extracted from the seeds using a mechanical pressing method, and its biodiesel was produced through transesterification with methanol in the presence of sodium hydroxide. The biodiesel yield was determined, and the major fuel properties, including viscosity, cetane number, density, and cold flow characteristics, were thoroughly analyzed. The results revealed that the biodiesel yield from A. mexicana oil was approximately 95.7 %, which is comparable to other non-food oilseeds. The fuel properties of the biodiesel, such as kinematic viscosity (5.03 cSt), cetane number (59.4), and density (884 kg/m3), were evaluated and compared with the ASTM D6751 and EN 14214 standards for biodiesel quality. The cold flow properties, including the pour point and cloud point, also met the specified limits for biodiesel use in colder climates. Furthermore, the fatty acid profile of the A. mexicana oil was determined through gas chromatography, revealing a composition of predominantly linoleic acid (C18:2), oleic acid (C18:1), and palmitic acid (C16:0). The fatty acid composition indicates that the biodiesel produced from Argemone mexicana has desirable characteristics for high-quality biodiesel production. Overall, the results suggest that A. mexicana oil is a viable and sustainable feedstock for biodiesel production, with fuel properties that meet international standards for biodiesel use.